Dual method cryptography image by two force secure and steganography secret message in IoT - Maisa'a Abid Ali K. Al-Dabbas; Ashwak Alabaichi; Ahmed Saleem Abbas (Universitas Ahmad Dahlan, 2020)
With the go on the evolution of both computer and internet technology, videos, sounds, and scripts are used more and more often. It can be used in sundry techniques in ciphering and data concealing. The objective of this paper is leading to the suggestion of a new method of the combination between encryption and concealment of information so as to make it difficult to identify the transmitted datavia networks. This study has used two force secure (2FS) to encrypt the images, in other words, the SF is frequent twice on the image, to obtain powerful encryption then the concealing of the secret message is done inside the cryptography of the image has been performed using a secret key (cosine curve), and this stego-encryption image has been transformed forthe Internet of things storage in the database in IoT (data flow), when the user needs any information can be access inviaof internet of things (IoTs). The outcome of the proposed system is obtained tobe evaluated through different measures, such aspeak signal noise ratio (PSNR), mean square error (MSE), entropy,correlation coefficient, and histogram. The proposed system is good, efficient, fast, has high security, robustness, and transparency.